Peningkatan peran serta masyarakat dalam upaya pencegahan dan pengobatan tuberkulosis di Sentajo Raya, Kabupaten Kuantan Singingi - Rita Endriani; Elda Nazriati; Ligat Pribadi Sembiring (Riau Journal of Empowerment, 2019)
The purpose of community service was to increase community participation in the prevention and treatment of tuberculosis (TB) through training of health cadres and the establishment of village TB posts in the working area of Sentajo Raya health centre. The activity method in the form of TB cadre training, the establishment of a Village TB Post and monitoring evaluation. The results of this activity were 30 people who had received training and were appointed as TB cadres. All TB cadres get TB module books, cadre pocketbooks and certificates. TB cadres must be able to play a role in the prevention and treatment of TB in their respective villages. The establishment of the first village TB post in the working area of Sentajo Raya Health Center was Pulau Kopung Sentajo Village. In the monitoring and evaluation activities of Pulau Kopung village Sentajo, a village TB post was formed in the "Village Population Activity Corner". Discussions with cadres and village heads were conducted to find out the problems faced, and there were activity books for cadres, PMO cards, and Banner TB for village TB posts. This activity can be carried out well and has the full support of the government and the community. They hope that this current activity and collaboration can be continued.